PHYSICAL METHODS OF EVALUATING THE LOAD OF FRICTION PAIRS OF BRAKING DEVICES (Part I) - Кіндрачук, Мирослав; Вольченко, Дмитро; Журавльов, Дмитро; Андрейчиков, Євген; Присяжний, Андрій (Problems of Friction and Wear, 2022)
The materials of the article refer to physical methods of assessing the load of friction pairs of braking devices. The methods are expressed by the principles affecting the physical and mechanical properties of materials of friction pairs and their internal and external parameters. The principles include: causality, symmetry, reciprocity and equivalence, kinship, superposition (elementary and complex). An analysis of the principles is performed and it is shown how they extend to the energy fields of brake friction pairs. From the principles, the following fields are selected in pairs: "mechanical-thermal"; "chemical-thermal"; and "electromagnetic". In the materials of this article, attention is paid only to the "mechanical-thermal" energy field during the electrothermomechanical frictional interaction of friction pairs of braking devices. It is known that the load on the friction pairs of belt-drum and disc-pad brakes depends on many subjective and objective factors. So, for the belt brake of the drilling winch, the objective factors are: drilling technology, climatic and physiological conditions; subjective - the quality of equipment manufacturing, qualification of service personnel, etc. For drum and disc-pad brakes of vehicles, the objective factors are climatic and road conditions; subjective - the quality of production of the braking mechanism as a whole, the qualifications of the driver, the technique of driving the vehicle, etc. It is quite clear that it is practically impossible to take into account all these factors in the mathematical description of the processes of heating elements of the brake assembly. The laws of elasticity, which take place during the contact-impulse interaction of the microprotrusions of the surfaces of metal-polymer friction pairs at small deformations, reflect mutually unambiguous dependencies between the impulse values ​​of stresses and deformations. Under the action of dynamic loads, electric and thermal currents, the surface layers of metal-polymer friction pairs undergo plastic deformations. studies and tests under mechanical loading of metal-polymer friction pairs allow to estimate normal forces, friction forces, dynamic coefficient of friction, braking torque developed by friction pairs and the intensity of wear of their working surfaces in a wide range of friction temperature changes, based on the fact that they have an impulse character , obeying the wave theory of the field. It is known that mechanical energy is an ordered form of energy, while internal energy is a disordered one.